Control interno y recaudación tributaria en la Municipalidad Distrital de Punchana 2025 - Valles Yndama, Xuxa Geraldine (2025)
The purpose of this research was to determine how internal control and tax collection are related in the Punchana 2025 District Municipality. Opting for a basic, quantitative, cross-sectional study with a non-experimental design, the sample consisted of 50 workers for the survey conducted with a questionnaire for data collection. The findings show that regarding the internal control variable, it was rated as "bad" by 14.0%, while 40.0% stated that it was average, and 46.0% stated that it was good. Regarding the tax collection variable, it was rated as "bad" by 10.0%, while 40.0% expressed that it was average, consequently, 50.0% stated that it is good. Likewise, the chi-square test yielded a significance value of 0.000 < 0.05. In conclusion, internal control is significantly related to tax collection in the Punchana 2025 District Municipality.